The Examination of Eating Attitudes of Fitness Individuals in Terms of Some Variables - Aydin Ilhan; Hayrettin Gumusdag (Journal of Educational Issues, 2024)
In this study, it was intended to examine the eating attitudes of individuals who do fitness in terms of some variables. Voluntary participation of 151 fitness individuals selected by random methods was ensured in the study. Information form of personal and Eating Attitude Test (YTT-40) were used to measure the eating attitudes of the individuals participating in the study. The Eating Attitudes Test (YTT-40) is a 6-point (Always, Very Often, Often, Sometimes, Rarely, Never) Likert-type scale consisting of 40 items based on self-report. It was developed to identify adolescents with eating disorders by Garner and Garfinkel (1979) and to measure the symptoms of anorexia nervosa, which can be applied to people older than eleven years of age, and the Turkish adaptation of this scale in Turkey was made by Savasir and Erol (1989). To determine the distribution of the participants’ socio-demographic information; Since descriptive statistics and T test and Anova test were used because the data showed normal distribution. As a result, it was determined that the eating attitudes of the participants showed an important difference in terms of gender and regularly participating in a bodybuilding program.